Organizational Citizenship Behaviour: Proposal for a New Dimension in Counsellor Education - Owen, Frances A.; Pappalardo, Salvatore J.; Sale, Carol A. (Canadian Journal of Counselling and Psychotherapy, 2007)
To survive in rapidly changing schools and human service organizations, counsellors must not only be competent clinicians, they must also be able to respond to a variety of informal work expectations. Organizational Citizenship Behaviour (OCB) is introduced from the organizational behaviour literature as a factor that contributes to the performance ratings of counsellors. Models of OCB are described and factors that encourage OCB are reviewed. A methodology for integrating OCB sensitization training into counsellor education programs is suggested as a means to prepare counselling interns for success as professional colleagues and employees.